2 Lifestyle behaviour outcome in heart failure prevention programme. (28th September 2016) - James, S; Tallon, E; Connell, D; O'Connell, E; Wilkinson, M; Watson, C; Gallagher, J; Ledwidge, M; McDonald, K
Abstract : Introduction: The St Vincent's Screening To Prevent Heart Failure (STOP-HF) Programme has shown to be clinical and cost effective. The use of RAAS modifying agents in part contributed to the reduction in the cardiovascular and heart failure endpoints. The impact of the strategy on lifestyle factors had not been fully examined. We aim to assess the lifestyle behaviour in the STOP-HF Programme. Methods: 739 at risk individuals attending the STOP-HF Programme were included. The characteristics, and lifestyle behaviour were recorded (Table 1 ). The lifestyle behaviour questionnaires were collected at two-time points, 2004 and 2010, included smoking, alcohol intake, salt intake, 30-minute walk, and exercise habits. The exercise habit was reported as intensity of exercise by multiplying the frequency with level of exercise. Frequency is determined as times in a week of minimum 20-minute exercise. Level of exercise is graded as 1 (mild), 1.5 (moderate) and 2.5 (strenuous). Results: The 30-minute walk habit change was not significant (−0.1466 ± 3.081 vs. 0.0842 ± 3.351). There were reduction of total alcohol intake/week in control arm (–2.041 ± 21.19) and intervention arm (−0.1277 ± 11.87), however not significant. Salt habit at table and during cooking also did not change significantly. Conclusion: Despite promising significant changes of reduction in smoking habit and increase in exercise intensity within each study arm, the between study arm changes are not significant. The alcohol intake, salt intake, and 30-minute walk habits did not change. These observations support the initial inference of RAAS modifying therapies role in the positive clinical outcome of STOP-HF Programme. These data should be use to guide focus on non-pharmacological strategies on heart failure.